MENINJAU ULANG DESENTRALISASI DI ERA SOEKARNO : ANTARA IDEALISME DAN KONTROL POLITIK - Zarma Hanifah; Aldri Frinaldi; Lince Magriasti; Hendra Naldi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to reexamine the dynamics of decentralization during President Soekarno’s administration, particularly in the Guided Democracy period (1959–1965), which was characterized by tension between democratic ideals and strong political control. Using a descriptive qualitative approach and the library research method, this study analyzes various academic literatures, legal documents, and historical sources relevant to the decentralization policy of that era. The findings reveal that although the government formally promoted regional autonomy through the enactment of Law Number 18 of 1965 on the Principles of Regional Government, its implementation instead reinforced the centralization of power in the hands of the central government. Regional leaders were directly accountable to the president rather than to the people, causing regional autonomy to lose its substantive meaning. Decentralization policies during Soekarno’s era functioned more as instruments of political stability and national integration than as mechanisms of local democratization. The hierarchical pattern of center–regional relations formed at that time continued throughout the New Order and was only corrected after the 1998 Reform era. This study concludes that decentralization without sufficient delegation of political and fiscal authority merely reproduces a new form of centralization. Therefore, the experience of the Guided Democracy period should serve as a reflection for modern decentralization policies to emphasize a balance between political trust, regional autonomy, and national integration.